Low-cost and precise inline pressure sensor housing and DAQ for use in laboratory experiments. (October 2020) - Goertzen, Luke; Mehr, Nicole; Lopez, Manuel; Udell, Chet; Selker, John S.
Graphical abstract: Abstract: There are many applications for inline pressure sensors, including fluid flow experiments, sensor field deployments, pumps, and Internet of Things systems. We developed a low-cost (~US$56), open-source, customizable inline pressure sensor system with operational flexibility and simple data logging. Most pressure sensors are expensive, not customizable, specific to a single tubing size, provide only analog readings, have poor stability and precision, or are incomplete without a data logger. These issues limit the usefulness of such hardware. Our system addresses all of these concerns. The customizability of both the hardware and firmware (via options or code modification) allows for the device to be tailored easily to each application. Tubing diameter, adapter dimensions, sensor used, logging behavior, and integration with other systems can be configured with ease. Much of the practicality and configurability of the software and hardware arise from the use of our Loom code and ecosystem. We present experimental data for the flow of a viscous fluid between two parallel plates that shows that sudden changes in fluid properties are not always discernible in static images, but are detectable as pressure signals with our inline pressure sensor.